The Role of High Concentrations of Homocysteine for the Development of Fetal Growth Restriction - Gaiday, Andrey; Balash, Lazzat; Tussupkaliyev, Akylbek (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective To assess homocysteine (Hcy) levels in the three trimesters of pregnancy in women with fetal growth restriction (FGR) and to evaluate the role of Hcy as a possible predictor of FGR.Methods A total of 315 singleton pregnant women were included in the present prospective cohort study and were monitored since the 1st trimester of pregnancy before delivery. Newborns were monitored for the first 7 days of life. Patients who had risk factors for FGR were excluded. Fetal growth restriction was defined according to uterine fundal height (< 10 percentile), ultrasound fetometry (< 5 percentile), and anthropometry of newborns (< 5 percentile). The concentrations of Hcy were detected at between 10 and 14, between 20 and 24, and between 30 and 34 weeks of pregnancy by enzyme-linked immunosorbent assay (ELISA). Receiver operating characteristics (ROC) curve test and diagnostic odds ratio (DOR) were performed to evaluate the results of ELISA.Results The concentration of Hcy in patients with FGR was 19.65 umol/L at between 10 and 14 weeks, compared with 9.28 umol/L in patients with normal fetal growth (p < 0.0001). The optimal cut-off level for Hcy in the 1st trimester of pregnancy was > 13.9 umol/L with AUC 0.788, sensitivity of 75%, specificity of 83.6%, and DOR of 15.2.Conclusion Assessment of serum Hcy concentration may be used as a predictor of FGR, with the highest diagnostic utility in the 1st trimester of pregnancy.
Keywords: fetal growth restriction; homocysteine; hyperhomocysteinemia; prediction of fetal growth restriction